1975
DOI: 10.1148/115.2.369
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of an Air-Filled Subdural Space During Nitrous Oxide Anesthesia

Abstract: The long-term administration of nitrous oxide anesthesia during craniotomy as well as following closure of the parietal craniotomy flap (under no tension) leads to significant expansion of the residual air bubble trapped under the dura. A case is presented in which an extracerebral avascular space, filled only with gas, caused a marked shift of the intracranial structures and uncal herniation secondary to nitrous oxide anesthesia during craniotomy and postcraniotomy angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…[ 9 17 ] Since then, N 2 O has been implicated as a cause of tension pneumocephalus in other case reports. [ 11 12 18 19 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 9 17 ] Since then, N 2 O has been implicated as a cause of tension pneumocephalus in other case reports. [ 11 12 18 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…Hence, with increased amount of intracranial gas, there is a severe and rapid increase in intracranial pressure (ICP), especially with a preexisting pneumocephalus. [ 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…The patient of M ali.amo el al. [7] developed subfalcial and uncal herniation following expansion of a surgically trapped intracranial air bubble, and Phillipart [9] showed that NoO anesthesia was especially hazardous when a space-occupying mass Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…Philippart et al (1968) suggested that the cerebrospinal fluid compartment is 'effectively indistensible', and explained the rise in pressure they observed as a direct result of this. Mallamo et al (1975) described considerable increase in size of a subdural air bubble remaining after a craniotomy while the patient was maintained under anaesthesia with 50% nitrous oxide. Gas embolism via ventriculoatrial shunts was described in two cases having air in the cerebral ventricles by Paul and Efyects of general anaesthesia on size of cerebrospinal fluid spaces Munson (1976); in one of these a cardiac murmur due to the gas in the shunt could be reproduced at will by reintroducing nitrous oxide to the inhaled gases!…”
Section: Discusandion Comparison Of Changes In Ventricular Size After Pmentioning
confidence: 99%
“…The explanation offered for these observations hinges on the much greater solubility of nitrous oxide as compared with nitrogen (by a factor of 34, according to Mallamo et al (1975)). The contrast medium (air) is effectively 80% nitrogen and 20% oxygen.…”
Section: Discusandion Comparison Of Changes In Ventricular Size After Pmentioning
confidence: 99%